(untitled) (Research, Society and Development, 2021)
Hormonal contraception is one of the most used by women in Brazil and the world. In Brazil, an estimated 23% of women with a reproductive age (10 to 49 years) are users of hormonal contraceptives. The most frequent side effects of these medications are: The most frequent side effects associated with these medications are: headache, nausea, vomiting, dizziness, irritability, increased appetite resulting in weight gain, changes in sexual appetite and fall handsome of hair. The lack of knowledge about the side effects arising from the continued use of oral hormonal contraceptives has affected its effectiveness, it is essential that these women are warned about the use of this contraceptive method, the most correct way to take them, who can or cannot use them and especially, correctly informing about the risks and benefits that oral contraceptives may have. This study aimed to demonstrate and report the knowledge of academics at the Faculty of Guaraí - TO, about the consequences of prolonged and continuous use of oral contraceptives, which are often used without a medical prescription. The role of health professionals is essential when it comes to guiding and indicating the ideal contraceptive for each woman, in order to avoid erroneous contraception and thus generating different effects and problems in each woman’s life.